Potential of invasive alien species Clidemia hirta as antibacterial against Salmonella typhi and Staphylococcus aureus - Mentari Putri Pratami; Miftahul Huda Fendiyanto; Rizky Dwi Satrio; I Dewa Ketut Kerta Widana; Isna Arofatun Nikmah; Nastiti Intan Permata Sari; Mo Awwanah; Nadya Farah; Didi Darmadi (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pratami MP, Fendiyanto MH, Satrio RD, Widana IDKK, Nikmah IA, Sari NIP, Awwanah M, Farah N, Darmadi D. 2021. Potential of invasive alien species Clidemia hirta as antibacterial against Salmonella typhi and Staphylococcus aureus. Biodiversitas 22: 3363-3369. Clidemia hirta D. Don is an invasive alien species (IAS) that is a threat to biodiversity in tropical country particularly Indonesia, and remains underutilized to date. Conversely, prevalence of typhus in Indonesia is generally higher every year. Thus, the aim of this study was to detect phytochemicals in ethanolic and aqueous extracts of C. hirta and their antibacterial activity against Salmonella typhi and Staphylococcus aureus. The research methods included sample identification, generating the simplicia, determination of water content, extraction, phytochemical screening tests, and antibacterial activity tests. Identification was made based on morphological characteristics. The water content in the dried powder of simplicia was 12.26 ± 0.39%. Phytochemical results showed that 70% ethanol extract of C. hirta contained flavonoids, saponins, tannins, and triterpenoids compounds. In addition, aqueous extract of C. hirta showed positive results on flavonoids, saponins, tannins, and steroids tests. Antibacterial activity results showed that ethanolic extracts of C. hirta inhibited S. typhi and S. aureus at all concentrations, while aqueous extract inhibited bacterial growth in only 12.5% ??and 25% concentrations. These findings indicate that C. hirta has antibacterial activity that inhibits S. typhi and S. aureus. This information can be used for adding preliminary data to metabolite interest researchers, i.e., biologists and biotechnologists in the future.